iRGD Peptide-Mediated Liposomal Nanoparticles with Photoacoustic/Ultrasound Dual-Modality Imaging for Precision Theranostics Against Hepatocellular Carcinoma - Li H (Dove Medical Press, 2021)
Huipu Li,1,* Shasha Shi,1,* Meng Wu,2,* Wei Shen,1 Jianli Ren,3 Zhechuan Mei,1 Haitao Ran,3 Zhigang Wang,3 Yi Tian,4 Jian Gao,1 Hongyun Zhao1,3 1Department of Gastroenterology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Ultrasound, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, People’s Republic of China; 3Chongqing Key Laboratory of Ultrasound Molecular Imaging, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Department of Plastic Surgery, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongyun Zhao; Jian Gao Email zhychina@cqmu.edu.cn; 982213482@qq.comPurpose: Prepare a multifunctional ultrasound molecular probe, cell-penetrating peptide-modified 10-hydroxycamptothecin-loaded phase-transformation lipid nanoparticles (iRGD-ICG-10-HCPT-PFP-NPs), and to combine iRGD-ICG-10-HCPT-PFP -NPs with low-intensity focused ultrasound (LIFU) for precision theranostics against hepatocellular carcinoma (HCC).Materials and Methods: The morphology of nanoparticles (NPs) and iRGD-ICG-10-HCPT-PFP-NPs was detected. In vitro, we examined targeting ability by flow cytometry and confocal laser scanning microscopy (CLSM), assessed penetration ability into hepatoma cells, and assessed killing ability. In vivo, we examined the targeting ability of the NPs with a photoacoustic (PA) imager and fluorometer (FL), while LIFU irradiation was used to trigger the release of chemotherapeutic drugs, which had a therapeutic effect on tumors.Results: The particle size of iRGD-ICG-10-HCPT-PFP-NPs was 298.4 ± 10.42 nm. In vitro, iRGD-ICG-10-HCPT-PFP-NPs bound more to SK-Hep1 cells than ICG-10-HCPT-PFP-NPs. iRGD-ICG-10-HCPT-PFP-NPs could achieve PA/ultrasound imaging. The percentage of antiproliferative and apoptotic cells in the iRGD-ICG-10-HCPT-PFP-NPs+LIFU group was significantly higher. In vivo, iRGD-ICG-10-HCPT-PFP-NPs can target tumor sites and achieve PA/ultrasound imaging. The tumor volume in the iRGD-ICG-10-HCPT-PFP-NPs+LIFU group was significantly smaller, and the antiproliferative and proapoptotic effects were higher.Conclusion: We successfully prepared a novel molecular probe that has good targeting, can perform ultrasound/PA dual-modality imaging, and can penetrate deep into tumors to achieve better therapeutic tumor effects, providing a new idea and method for theranostics of HCC.Keywords: molecular probe, homing membrane peptide, precision diagnosis and treatment, dual-modality imaging